2020
DOI: 10.30699/ijp.2020.121365.2320
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine S-methyltransferase and Pemphigus Vulgaris: A Phenotype-Genotype Study

Abstract: Scan to discover online Background & Objective: Thiopurine drugs are considered as a treatment modality in various autoimmune disorders including pemphigus vulgaris (PV). These drugs are metabolized by an enzyme "Thiopurine S-methyl transferase" (TPMT). Various variants of this enzyme may have decreased activity leading to serious drug side effects. To investigate the phenotype and genotype of TPMT in PV patients receiving thiopurine drugs. Methods: A total of 50 patients (29 women and 21 men) with pemphigus v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…TPMT ∗ 2, TPMT ∗ 3A, TPMT ∗ 3B, and TPMT ∗ 3C are inactivating alleles that explain 80% to 95% of individuals with lower TPMT activity. The most common subtypes such as TPMT ∗ 3A and TPMT ∗ 3C showed less frequency in our population according to different studies [ 38 , 39 ]. Furthermore, results of previous Iranian studies revealed that there were no signs of both defective alleles in the population [ 38 ].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…TPMT ∗ 2, TPMT ∗ 3A, TPMT ∗ 3B, and TPMT ∗ 3C are inactivating alleles that explain 80% to 95% of individuals with lower TPMT activity. The most common subtypes such as TPMT ∗ 3A and TPMT ∗ 3C showed less frequency in our population according to different studies [ 38 , 39 ]. Furthermore, results of previous Iranian studies revealed that there were no signs of both defective alleles in the population [ 38 ].…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, results of previous Iranian studies revealed that there were no signs of both defective alleles in the population [ 38 ]. A study on Pemphigus Vulgaris patients taking AZA showed no TPMT ∗ 2 or TPMT ∗ 3C mutant alleles and none of the subjects developed hepatotoxicity and bone marrow suppression [ 39 ]. Therefore, we carefully monitored the patients' blood counts every month, and if signs of reduction in blood counts were observed, the TPMT test was ordered.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, TPMT phenotype testing is fairly common in some countries ( Fargher et al, 2007 ; Weitzel et al, 2018 ). However, it is worth noting that TPMT enzyme activity is usually measured in fresh red blood cells directly ( Mokhtari et al, 2020 ), or consumes a longer turnaround test time ( Weitzel et al, 2018 ). Moreover, in patients who have received blood transfusions recently or in leukemia patients, because of atypical hematopoiesis, the result could not reflect the true enzymatic activity ( Mokhtari et al, 2020 ).…”
Section: Pharmacogenetics Of Thiopurinesmentioning
confidence: 99%